Національна та етнічна ідентичність українців Мараморощини (Румунія): проблеми та перспективи дослідження - Зан, М. (Народна творчість та етнографія, 2006)
The paper studies some problem of ethnocultural and national identification of Ukrainians of Maramuresh District of Romania during the last time. The author inform the main results of the third stage of project "The Ukrainian minority of the North-West of Romania". The author has analyzed statistics sources, interviews and questionnaires. A conclusion is made concerning to the high level of national (rumanian) consciousness of Ukrainians. The ethnosocial investigation demonstrate "the drifting" of ethnocultural identification of Ukrainians in this region. The author gives the conclusion about the perspectives of research of ethnosocial, ethnocultural and ethnopolitical life of the Ukrainians in Romania.